2011
DOI: 10.1039/c0mb00166j
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of statin effectiveness by copper and zinc in yeast and human cells

Abstract: Summary Lovastatin and other statins inhibit HMG-CoA reductase, which carries out an early step in the sterol biosynthesis pathway. Statins lower cholesterol and are widely prescribed to prevent heart disease, but like many drugs, they can interact with nutritionally acquired metabolites. To probe these interactions, we explored the effect of a diverse library of metabolites on statin effectiveness using a Saccharomyces cerevisiae model. In yeast, treatment with lovastatin results in reduced growth. We combine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 45 publications
1
14
0
Order By: Relevance
“…Here, statins substantially lowered the level of ergosterol and (in most instances) much more strongly the levels of all its triterpene precursors (Table 1). This is in accordance with the results of Fowler et al [27] showing a profound decrease of ergosterol level and an even deeper depletion of its precursors in lovastatin-treated yeast cells. Both these results indicate that following HMGR inhibition the yeast cell, whether it expresses the native enzyme [27] or the human one (this work), increases the rate of precursor conversion into ergosterol in an attempt to maintain the supply of this vital sterol.…”
Section: Discussionsupporting
confidence: 93%
“…Here, statins substantially lowered the level of ergosterol and (in most instances) much more strongly the levels of all its triterpene precursors (Table 1). This is in accordance with the results of Fowler et al [27] showing a profound decrease of ergosterol level and an even deeper depletion of its precursors in lovastatin-treated yeast cells. Both these results indicate that following HMGR inhibition the yeast cell, whether it expresses the native enzyme [27] or the human one (this work), increases the rate of precursor conversion into ergosterol in an attempt to maintain the supply of this vital sterol.…”
Section: Discussionsupporting
confidence: 93%
“…Perhaps more interesting is that the observed reduction in parasite growth might be a direct effect of statins on the L. major HMG-CoA reductase 26 . Several other studies have reported a direct anti-fungal role for statins in extracellular culture 27 28 29 . In contrast, we observed no effect on extracellular growth of L. major promastigote parasites in presence of simvastatin at various concentrations tested (data not shown).…”
Section: Discussionmentioning
confidence: 90%
“…We extracted metabolites (Supplemental Note) and performed derivatizations as previously described (Fowler et al 2011). All metabolite analysis was done on a Leco Pegasus 4D system (GC3GC-TOFMS).…”
Section: Phenotypingmentioning
confidence: 99%